Effects of Sr doping on the structure, magnetic properties and microwave absorption properties of LaFeO3 nanoparticles. Issue 17 (1st December 2020) - Huang, Lei; Cheng, Lichun; Pan, Shunkang; He, Yu; Tian, Chuang; Yu, Jingjing; Zhou, Huaiying
Abstract: Lightweight, broadband microwave absorbing materials, with strong absorption capacities, are an urgent demand for practical applications. The microstructural and microwave absorption properties of LaFeO3 samples prepared by a sol-gel method using different amounts of Sr are investigated systematically. X-ray diffraction and Rietveld refinement studies showed that Sr 2+ doping can distort the crystal structure of LaFeO3, leading to lattice expansion and spin tilt of the Fe-O-Fe bond angle. The improvement of magnetic properties mainly originates from the synergistic effect of the bond angle spin tilt and crystal structure defects. Oxygen vacancies will be generated due to the fluctuations in the valence state of Fe 3+ resulting from the substitution of La 3+ by Sr 2+ as deduced from the X-ray photoelectron spectroscopy analysis. The generation of oxygen vacancies, electronic hopping and polarization loss may be one of the main reasons for changes in the electromagnetic parameters. The minimum reflection loss ( RL ) of La1– x Sr x FeO3 nanoparticles with the Sr doping of 0.2 can reach approximately -39.3 dB at 10 GHz for the thickness of 2.2 mm, and the effective absorption bandwidth ( RL ≤ -10 dB) can reach approximately 2.56 GHz. In addition, the La1– x Sr x FeO3 nanoparticles also can obtain better microwave absorbing performance in the C-band (4–8 GHz) with the minimum RL of -36.8 dB for the matching thickness of 3.0 mm and Sr content of 0.3. Consequently, La1– x Sr x FeO3 nanoparticles are promising materials for use in a high-performance and adjustable electromagnetic wave absorber, particularly in C-band and X-band.